Elderly and their barriers to accepting and learning to use technology: A scoping review - Najmi Najiha Mohd Zaid; Nahdatul Akma Ahmad; Muhammad Fairuz Abd Rauf; Azaliza Zainal; Fariza Hanis Abdul Razak; Tengku Shahrom Tengku Shahdan; Lim Seong Pek (Faculty of Social and Political Science, Universitas Airlangga, 2023)
As the rate of technology development is concurrently increasing with the number of elderly people, it is necessary for people to be digitally literate and be able to use technology to its full capacity. However, research has found that the digital divide is still happening within the community, as not everyone has fully accepted technology in their daily life routines. With the aim of identifying barriers and challenges of elderly learning technology, and mitigating efforts used by past researchers to cater to the barriers, a scoping review following the Preferred Reporting Items for Systematic Reviews and Meta-Analysis Extension for Scoping Reviews (PRISMA-ScR) guideline was conducted, and 19 eligible articles have identified having low self-confidence, lack of knowledge, cognitive and physical limitations, as well as psychological and socioeconomic challenges as the common barriers associated with elderly learning. Recognizing what the elders can and cannot do, alongside having intervention programs that promote digital inclusion, could be taken as measures to mitigate the barriers faced by the elders in learning to use technology.